Sedekah Bumi Tradition: Harmonizing Values Moral Education And Local Wisdom Based On Socio-Cultural Literacy (In Sumber Sari Kepahiang) - Maryati, Ana; Ulandari, Tri; Salsabila, Salsabila (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
This research aims to explore and analyze how the Sedekah Bumi tradition in Sumber Sari Village Kepahiang-Bengkulu contributes to the formation of moral education values in the community. In addition, this research also aims to harmonize the extent to which the local wisdom contained in the tradition contributes to the moral and ethical values taught in socio-cultural literacy-based education. With this understanding, it is hoped that effective ways can be found to integrate local traditions with moral education to increase social awareness and community responsibility. This research uses a qualitative research method with an ethnographic approach to deeply understand the tradition of Sedekah Bumi in Sumber Sari Village Kepahiang and how the tradition facilitates the harmonization of moral education values and local wisdom in the context of socio-cultural literacy. The data collection techniques used include observation, interviews, and documentation studies. The results showed that the Sedekah Bumi tradition plays a significant role in teaching moral values such as togetherness, gratitude, and social responsibility through ritual practices that involve the entire community.